Prospects and Challenges of the Protection and Enforcement of Registered and Unregistered Trademark Rights Within the OAPI Sub-Region - Vanessa, Ebai Arrey (Law and Economy, 2026)
This study critically examines the prospects and challenges of protecting and enforcing registered and unregistered trademark rights within the Organisation Africaine de la Propriété Intellectuelle (OAPI) sub-region. Anchored in institutional theory and the economic incentive theory of trademarks, the research explores how legal harmonization through centralized registration interacts with decentralized national enforcement mechanisms to shape practical outcomes. Drawing on doctrinal analysis of the Bangui Agreement, national laws, and international treaties including TRIPS and the Paris Convention, the study assesses the effectiveness of civil, criminal, administrative, and border enforcement mechanisms. Findings reveal that while the OAPI framework provides strong legal protection for registered trademarks, enforcement effectiveness is uneven due to institutional weaknesses, procedural delays, limited judicial expertise, and inadequate protection for unregistered marks, particularly affecting informal and small-scale businesses. The study identifies systemic challenges including fragmented enforcement, high litigation costs, and low stakeholder awareness, which undermine the broader objectives of trademark law. Based on these findings, the research proposes context-specific recommendations to strengthen institutional capacity, harmonize enforcement procedures, expand protection for unregistered trademarks, and enhance awareness among stakeholders. The study contributes to knowledge by offering a nuanced analysis of OAPI’s hybrid intellectual property regime, highlighting enforcement gaps, and providing practical insights for policy reform, judicial practice, and regional cooperation, thereby advancing understanding of trademark protection and economic development in African regional IP systems.